2022
DOI: 10.1111/raq.12713
|View full text |Cite
|
Sign up to set email alerts
|

Influence mechanisms of macro‐infrastructure on micro‐environments in the recirculating aquaculture system and biofloc technology system

Abstract: Aquaculture intensification has emerged as a potential sustainable aquaculture strategy to contribute to the Food and Agriculture Organisation's United Nations Sustainable Development Goals associated with food security. Recirculating aquaculture systems (RASs) and biofloc technology systems (BFTs) are typical land-based intensive aquaculture facility models that have been widely researched and applied.The rapid growth of both systems has boosted human nutrition and the regional economy but has also caused con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 185 publications
(365 reference statements)
0
13
0
Order By: Relevance
“…However, these investigations were mainly focused on the effect of single factors on the tank performance and did not consider the possible effect of turbulence generated by the interaction between the jetting position and the jetting angle. Significantly, Zhao et al (2022) pointed out that flow velocity in culture tanks can be adjusted to provide much higher swimming speeds and thus effectively exercise fish. Therefore, the design of the velocity must meet the self-cleaning ability and speed requirements of the fish growth jointly in actual aquaculture engineering.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, these investigations were mainly focused on the effect of single factors on the tank performance and did not consider the possible effect of turbulence generated by the interaction between the jetting position and the jetting angle. Significantly, Zhao et al (2022) pointed out that flow velocity in culture tanks can be adjusted to provide much higher swimming speeds and thus effectively exercise fish. Therefore, the design of the velocity must meet the self-cleaning ability and speed requirements of the fish growth jointly in actual aquaculture engineering.…”
Section: Discussionmentioning
confidence: 99%
“…Generally, aquaculture tanks are fabricated in five geometries, including rectangular, circular, octagonal, rectangular round chamfering, and runway. Among these geometries, octagonal tanks are easier to handle and construct than other tanks so that octagonal tanks have been more common in operational production (Zhao et al, 2022). Davidson and Summerfelt (2004) studied the effects of the inlet structure on the self-cleaning features of large circular aquaculture tanks and found that the appropriate direction of the inlet structure increases the rotation velocity in the tank.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…With regard to Conceptualizing and/or designing circular production systems , we called for ‘Circular production systems, such as aquaponics, integrated multi‐trophic aquaculture systems, etc.’. For this topic, four interesting reviews emerged, one relevant for marine aquaculture, 18 two relevant for inland aquaculture 19 and one for both 20,21 . Some lesser known approaches were taken to the forefront by Garibay‐Valtez et al, 20 Lothmann and Sewilam, 18 and Zhao et al, 21 while promising solutions were revisited from a wider industry perspective by Marousek et al 19 …”
mentioning
confidence: 99%
“…For this topic, four interesting reviews emerged, one relevant for marine aquaculture, 18 two relevant for inland aquaculture 19 and one for both 20,21 . Some lesser known approaches were taken to the forefront by Garibay‐Valtez et al, 20 Lothmann and Sewilam, 18 and Zhao et al, 21 while promising solutions were revisited from a wider industry perspective by Marousek et al 19 …”
mentioning
confidence: 99%